The protective effects of lycopene on the loss of body weight and histopathological lesions in liver, kidney, heart, and brain tissue of rats exposed to subchronically differential doses of 2,3,7,8-tetrachlorodibenzo-p-dioxin - Sakin, Fatih; Çeribaşi, Ali Osman; Servi, Kadir; L?cr?mioara, Popa (My University, 2011)
The aim of this study was to investigate the possible protective role of lycopene (LYC) on body weight changes, and histopathological lesions on liver, kidney, heart, and brain tissue in male rats exposed to subchronically differential doses of 2,3,7,8-tetrachlorodibenzo-p-dioxin (TCDD), a highly toxic xenobiotic. Forty-eight rats were divided into six groups. The first group received 0.5 mL corn oil as control; the second group was treated with10 mg/kg bw/day LYC. Groups 3 and 4 were treated with 50 and 500 ng/kg bw/day of TCDD, respectively. Groups 5 and 6 were subjected to 50 and 500 ng/kg bw/day of TCDD along with 10 mg/kg bw/day of LYC, simultaneously. The period of the experiment was 13 weeks. In TCDD-treated groups, a dose-related depression of mean body weight was observed when compared to control. Simultaneously LYC administration reduced the loss of body weight and partially or totally recovered the formed histopathological lesions in liver, kidney, and heart tissue of rats exposed to TCDD. As a result, it is suggested that LYC has a protective effect against the loss of body weight and toxicity caused by TCDD.
Keywords: Dioxin; Histopathology; Lycopene; Toxicity